Effects of TNF-α inhibition on pre-clinical enthesitis: observational study on 49 psoriatic patients. (3rd April 2022) - Narcisi, Alessandra; Valenti, Mario; De Simone, Clara; Esposito, Maria; Richetta, Antonio; Teoli, Miriam; Argento, Giuseppe; Costanzo, Antonio
Abstract: Background: Enthesitis is a hallmark of psoriatic arthritis (PsA) and echographic ultrasounds (US) represent a support for diagnosis of pre-clinical signs of enthesitis in asymptomatic patients at high risk for advanced forms. Early treatment with anti-TNFα could prevent permanent damage contrasting the degenerative course of the disease. Objectives: To evaluate the effects of adalimumab on echographic and preclinical enthesitis signs in patients affected by plaque psoriasis. Methods: 49 psoriatic patients undergoing adalimumab treatment for plaque-type psoriasis were subjected to echographic screening for identifying pre-clinical signs of enthesitis. Patients underwent clinical and ultrasonographic examination of hands, elbows and knees before starting adalimumab and after 24 and 48 weeks of treatment. Results: We observed a reduction of the total number of echographic abnormalities and a significant decrease of the thickness of quadriceps tendons at week 24 and week 48. Furthermore, there was no evidence of significant articular damage progression during the entire study duration. Conclusions: Entheseal ultrasonography may be used for preclinical diagnosis of PsA. Our study demonstrates that early detection and management with adalimumab leads to a block of articular damage progression. On quadriceps tendon, adalimumab has shown to be effective with a significant thickening reduction at week 24 and 48